DESENTRALISASI SEBAGAI UPAYA PENANGGULANGAN PROBLEMATIKA SERTA TANTANGAN DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Annisa Fitria Jasmine Putri; Mutiara Herdika; Xena Alvina Fendita; Fratiwi (BULLET : Jurnal Multidisiplin Ilmu, 2022)
A normative legal literature study has been carried out on Law Number 23 of 2014 concerning Regional Government, which regulates the authority to administer autonomous regional government which is formed in two aspects of autonomy. First, full autonomy is all government affairs and functions concerning the content of the substance or the procedures for its implementation. Second, incomplete autonomy is a region that only controls the procedures for its implementation, but does not control the contents of its government. The research method used is a normative legal research method against Law Number 23 of 2014 concerning Regional Government. The background of this research is considering that Indonesia is a legal state that upholds the constitution, namely where the Law of Regional Government and Regional Autonomy is one of the laws that regulates how law enforcement is carried out in an area. This study aims to determine the implementation of existing provisions in regional government law and regional autonomy itself in the form of decentralization as an effort to overcome problems and challenges in the administration of regional government. Where in it involves four aspects, namely: 1). The urgency of decentralization, which is stated in article 1 number 6 of Law no. 23 of 2014 which among other things "regional autonomy is the right, authority, and obligation of an autonomous region to regulate and also manage all government affairs on their own along with the interests of local communities in the context of the Unitary State of the Republic of Indonesia." Likewise, decentralization can be trusted as a tool whose task is to unite the state and local communities, as well as to encourage community empowerment, community creativity and the development of aspirations; 2). Decentralization problems, namely various kinds of problems that exist in autonomous regions that result in overlapping authorities. Local governments must also have competent state apparatus in their fields to improve local government performance; 3). Challenges of Decentralization, which are related to regional competence and performance in using APBD, Transfers to regions and village funds are not optimal, Central and regional synergies are not optimal, regional tax ratios still need to be increased, Public infrastructure spending is still low, Number of types of programs and too many activities, and the local government has not optimized access to alternative financing to fund regional development needs; 4). Efforts to Overcome Problems and Challenges, namely the implementation of revitalization as part of the decentralization process as well as regional autonomy, it is deemed necessary to realize the implementation of decentralization policies consistently and also to improve the performance of local governments through efforts to establish legislation and also work instruments for implementing the Act. Number 32 of 2004. Thus, it can be concluded that the Unitary State of the Republic of Indonesia is a legal state based on Pancasila and the 1945 Constitution in which it is structured regarding autonomous regions that support the formation of a unified state and national unity.